2022
DOI: 10.1155/2022/8422903
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Acceptance and Commitment Therapy Combined with Music Relaxation Therapy on the Self-Identity of College Students

Abstract: This paper analyzes various effects of acceptance and commitment therapy combined with music relaxation therapy on the self-identity of the college students. Through open recruitment and following the principle of voluntary and confidential, 80 college students were selected from our school, and then they were divided into two groups: the control group (40 cases) and the observation group (40 cases). The observation group received acceptance and commitment therapy combined with music relaxation therapy. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Previous research also proved this suggestion. The spirit of cooperation in musical activities is easily transferred to real life, which helps most pessimistic and self-enclosed students to open their hearts, improve their ability to communicate and understand others, and build good interpersonal relationships while knowing themselves correctly [7][8] . The visitors' ability to get along with the therapist improved in individual music therapy, and that they felt cared for in the therapy, which in turn led to them feeling supported in their adjustment to university life and further better adjusted to their new university life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also proved this suggestion. The spirit of cooperation in musical activities is easily transferred to real life, which helps most pessimistic and self-enclosed students to open their hearts, improve their ability to communicate and understand others, and build good interpersonal relationships while knowing themselves correctly [7][8] . The visitors' ability to get along with the therapist improved in individual music therapy, and that they felt cared for in the therapy, which in turn led to them feeling supported in their adjustment to university life and further better adjusted to their new university life.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent depression is being combated with music therapy in different institutions because it helps to improve emotions and achieve positive effects with the tasks assigned [24], music therapy is a strategy of effective results that reduce stress, which were realized by combining together with virtual reality using mobile applications [25] whose acceptance by university students is voluntary and positive because the effects were positive mental state, mental resilience, improved quality of life, self-identification and the elimination of depression [26], this effect is occurring at the level of university students managing to detect moderate and mild cases and treated before having more bad repercussions [27], because since the arrival of Covid-19 music therapy has been occurring with an infinite number of virtual formats (asynchronous and synchronous) [28].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%